PEMANFAATAN SEKAM PADI DALAM PEMBUATAN BRIKET SEKAM SEBAGAI ALTERNATIF PENGGANTI MINYAK TANAH - Efratenta Katherina Depari; Saprinurdin -; Deselina - (Universitas Bengkulu, 2018)
The purpose of the community service activity is to obtain alternative fuel, reduce waste rice husk, rice husk value-added so that it becomes more useful and reduce the illegal logging. This community service activity is done from August - September 2014 in the village of Srikaton, District of Pondok Kelapa, Central Bengkulu. The target of this activity is PKK members, members of the youth institution and farmer group members. The methods used in this activities are counseling, training and demonstration. Rice husk briquette as an alternative kerosene in the village Srikaton is one right step in the processing of agricultural waste. Rice husk briquette is also one way that can be used by housewives, especially to save money in the purchase of fuel for cooking needs. Keywords: rice husk, rice husk briquette, kerosene, Srikaton